EVALUATION OF THE CYTOTOXICITY OF EUGENIA KLOTZSCHIANA O.BERG EXTRACTS BY THE ARTEMIA SALINA LETHALITY ASSAY (CIPEEX, 2022)
THE FLORA OF THE CERRADO PRESENTS ITSELF AS A POCKET OF BIOACTIVES, STILL LITTLE EXPLORED. AND AS A RESULT OF THE ENVIRONMENTAL IMPACTS THAT THIS BIOME HAS SUFFERED OVER TIME, MANY SPECIES AND MANY BIOACTIVE POTENTIALS ARE BEING LOST WITHOUT BEING KNOWN. THE SPECIES EUGENIA KLOTZSCHIANA O.BERG STILL HAS A SMALL NUMBER OF STUDIES, SO WE SOUGHT TO EVALUATE THE CYTOTOXIC POTENTIAL OF ITS ETHANOLIC AND HEXANOLIC EXTRACTS IN THE ARTEMIA SALINA LETHALITY TEST. WE IDENTIFIED THAT THE HEXANIC EXTRACT SHOWED BIOACTIVITY IN LOWER VALUES - CL50 - 0.5921 MG.L-1 THAN THE ETHANOLIC - 1.2245 MG.ML-1. THROUGH THESE RESULTS WE IDENTIFY THE BIOACTIVITY OF SUCH EXTRACTS AND SUGGEST NEW STUDIES TO KNOW THEIR BIOACTIVE POTENTIALS.
Keywords: artemia salina lethality assay; cytotoxicity; evaluation